COMPARATIVE ANALYSIS OF THE LAND ADMINISTRATION IN UKRAINE AND THE EUROPEAN UNION - , К. А., М. А. (Municipal economy of cities. Series: «Economy science», 2017)
The origins of regulation of land relations go back centuries. All this time they evolve with the development of modern civilization. Unfortunately, Ukraine is a young state and has made its experience with obsolete systems and technologies of the USSR. As a result, there is a difference in terminology in the field of land management. For example, the absence of the word «land management» from other European states. Our understanding and definition of «land management», as a system of measures to organize the rational use and protection of land, is different to most foreign countries, despite the fact that all land management activities take place. Therefore, the application in Ukraine of the experience of other countries more developed in this matter is a necessary step for the development of Ukrainian land management. Keywords: land administration, land management, inventory, intellectual information technologies, land relations, mathematical models.